Analisis Penerapan Prinsip – Prinsip Good Governance dalam Pelayanan Publik di Kantor Desa Perboto Kecamatan Kalikajar Kabupaten Wonosobo - Abdurrosyid, Muhammad; Eldo, Dwian Hartomi Akta Padma (Jurnal Studi Pemerintahan dan Akuntabilitas, 2024)
Purpose: The purpose of this research is to find out how the procedures for applying the principles of good governance in public services and how the inhibiting and encouraging factors for applying the principles of good governance in public services at the Perboto village office, Wonosobo Regency Research methodology: The research method used is qualitative research methods that try to explain or describe in as much detail as possible the objects and research problems based on the facts obtained in the field. This research uses the following data collection techniques to get primary and secondary data: literature studies, field studies, observations, interviews, and documentation. Results: Based on the results of the survey and discussion regarding the application of the principles of good governance in public services at the Perboto Village Office, Kalikajar Subdistrict, Wonosobo Regency by using an analysis of several principles of good governance consisting of transparency, accountability, rule of law, participation, government responsiveness, strategic vision, application of the principles of strategic vision in public services, government effectiveness and efficiency, justice, and consensus-oriented in solving various problems. Limitation: Limitations or weaknesses in this study lie in the research process or during interviews, researchers realize that in a study there must be something missing and many weaknesses. Contribution: In order to improve understanding and develop knowledge, further efforts are needed to apply the principles of good governance in the lecture environment. This paper is expected to be a recommendation or additional reference for future researchers, especially for those who want to apply the principles of good governance in their studies.